Educational Environment in Operating Theatres of Bangladesh: Views of Surgical Trainees and Trainers (Bangladesh Journal of Medical Education, 2023)
The quality of the educational environment in the operating theatre is one of the key determinants for the effective training of surgical trainees. This descriptive cross-sectional study was aimed to evaluate the views of postgraduate surgical trainees and their trainers to identify the strength and weaknesses of the educational environment of the operating theatres of Bangladesh. Data were collected by physical means from 349 surgical allied trainees of 14 different disciplines who are having a minimum of three months of working experience in operating theatre as postgraduate trainees. To evaluate the perception of trainees’ internationally validated questionnaire STEEM consisting 40 items was used. To highlight the perspective of Bangladesh, an additional self-made questionnaire consisting ten items was also used. Both questionnaires have five answering options (1-5) for each item as per Likert scale. A score of 60% was considered as satisfactory. To have more vivid ideas six sessions of focus group discussion with trainees and12 in-depth interviews of trainers with minimum five years of teaching experience in his/her specialty from most of the surgical disciplines were also carried out. In this study, the reliability score of STEEM and the self-made questionnaires were 0.757 and 0.730 respectively as determined by Cronbach’s alpha. In general, the perception of trainees regarding the educational environment in OT of Bangladesh was grossly satisfactory with a mean score of STEEM 134.32±14.05 (67%) and 36.80±5.25 (73%) for self-made questionnaire. But group D subscale of STEEM (workload, support and supervision) failed to reach satisfaction level with a mean score of 20.89±5.36 (52%) and the difference between the four subgroups of STEEM was statistically significant. The satisfaction level of juniors in group B subscale of STEEM (perception of learning opportunities) was significantly higher than seniors. The perception between trainees of different disciplines was also statistically significant. From focus group discussions of trainees and in-depth interviews of trainers, this study revealed that trainees’ felt deprived of ‘hands on’ training and perioperative briefing either due to the huge workload or long learning curves of the junior faculties. Quality of training is somehow neglected due to physical absence of faculty members after routine office hour and also because of deficient simulation or skill lab. Trainees also claimed that their financial hardship making them bound for extracurricular activities compromising their full-time residential training.The overall educational environment in operating theatres of Bangladesh as perceived by trainees and trainers is satisfactory. To ensure the full engagement of the trainees under the direct supervision of faculties curriculum should be upgraded with the provision of a modern skill lab, workload should be managed and their financial issues need to be addressed sympathetically by the appropriate authority.Bangladesh Journal of Medical Education Vol.14(2) July 2023: 33-44